Third-party intervention (Revista do Tribunal Regional Federal da 3ª Região, 2016)
SUMMARY: I- Intervention by third parties. 1 - Concept and cases of appropriateness. II- Assistance. 2. concept. 3. preconditions for intervention. 4) Simple and joint legal assistance. 5. powers and procedural burdens of simple and joint legal assistants 6. the assistant's burdens and the limits of its action. 7. appeals. 8. atypical or negotiated assistance. 9. appeals by aggrieved third parties. III- Denunciation of jurisdiction. 10. concept. 11 - Obligation to report a claim. 12) Cases in which the notice of claim is not appropriate. 13. Purpose of the incident. 14. procedure. 15. effects of the notice of claim. 16. Compliance with the judgment accepting the claim. 17. Enforcement of the judgment. 18. Successive complaints. IV- Summons. 19. Concept. 20. Cases of admissibility of the incident (art. 130 of the NCPC). 21. Procedure. 22. Summons in civil liability insurance cases. V- Incident of disregard of legal personality. 23. Disregard of legal personality. 24. Inverse disregard of legal personality. 25. Procedure for the incident of disregard of legal personality. 26. Prevention of fraud. VI- Amicus curiae. 27. concept. 28. powers of the amicus curiae: oral argument and appeals.
Keywords: Intervention by third parties; CPC 2015; Assistence; Denunciation of jurisdiction; Summons